Pengaruh Kecerdasan Emosional, Motivasi Belajar dan Perilaku Belajar Terhadap Pemahaman Akuntansi - Apryani, Ida Ayu Santy; Indraswarawati, Sang Ayu Putu Arie; Pratiwi, Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2025)
Understanding accounting is the extent of the ability to understand accounting both in practice and theory. This study aims to determine the influence of emotional intelligence, learning motivation and learning behavior on accounting understanding. The population in the study was student of the Accounting Department who where still active and had finished taking financial accounting courses with the sample used being 77 respondents. The research method use is quantitative. The data analysis techniques used in this study are multiple linear regression, coefficient of determination, F test and t test. Based on the results of the study, it can be seen that (1) emotional intelligence has a positive and significant effect on accounting understanding, (2) learning motivation has a positive and significant effect on accounting understanding, (3) learning behavior has a positive and significant effect on understanding, the influence of independent variables on accounting understanding is 94,7%.